PENERAPAN ARSITEKTUR NARATIF PADA MUSEUM DE GROTE POSTWEG DI KOTA BANDUNG - Nizar Firdaus Usman; Denny Husin (Jurusan Arsitektur dan Perencanaan, 2022)
The Anyer-Panarukan post road was a monumental colonial project with the aim of connecting areas on the northern coast of Java Island whose the benefits can still be felt today. The phenomenon that occurs along with the times is the erosion of the community’s collective memory about the origin of the post road. This is caused by the socio-cultural changes by the people along the road which which have slowly shifted the function and image of the post road. In adition, the existence of toll roads also makes it no longer the only choice for people to travel. The purpose of the project “De Grote Postweg: Sequential Narrative Space of The Great Post Road” is to retell the history of the origins of these monumental project, reflections, dan resolutions towards the future, through historical tourism, in the midst of massive changes and along the northern coast of the Island of Java. The choice of the city of Bandung as the location of the museum is based on the historical narrative of the city which intersects with the construction of the road at that time. The method used in designing this museum is narrative architecture in the typology of museum exhibition space. The project begins with grouping the historical time span of the road which is divided into 5 permanent exhibition space zones based on time sequence, which are then narrated in the form of spatial space with different keywords according to their respective historical narratives. The result of rethinking the typology of museum exhibition space with narrative architecture is an exhibition space that is organized according to the chronological historical events that is educative, attractve, and inclusive. Keywords: history; museum; narative; tourism; typology AbstrakJalan raya pos Anyer-Panarukan merupakan proyek monumental zaman kolonial dengan tujuan untuk menghubungkan daerah-daerah di pesisir Utara Pulau Jawa yang manfaatnya masih dapat dirasakan hingga masa kini. Fenomena yang terjadi seiring dengan perkembangan zaman adalah terkikisnya memori kolektif masyarakat tentang asal usul jalan raya pos tersebut. Hal ini disebabkan oleh perubahan sosial-budaya masyarakat di sepanjang jalan raya tersebut yang turut menggeser fungsi dan citra jalan raya secara perlahan. Selain itu, adanya jalan tol juga menjadikannya bukan lagi satu-satunya sebagai pilihan orang untuk bepergian. Tujuan dari proyek “Museum De Grote Postweg: Ruang Narasi Berurutan Jalan Raya Pos Besar” di Kota Bandung adalah menceritakan kembali sejarah terbentuknya proyek monumental tersebut, refleksi, dan resolusi menuju masa depan melalui pariwisata sejarah di tengah masifnya perubahan di sepanjang pantai Utara Pulau Jawa. Pemilihan Kota Bandung sebagai lokasi museum tidak lepas dari narasi sejarah Kota Bandung yang saling bersinggungan dengan pembangunan jalan raya pos pada saat itu. Metode yang digunakan pada perancangan museum ini adalah arsitektur naratif pada tipologi ruang pamer museum. Perancangan dimulai dengan pengelompokan rentang waktu sejarah jalan rata pos yang dibagi menjadi 5 zona ruang pamer tetap berdasarkan urutan waktu, yang kemudian dinarasikan dalam bentuk ruang spasial dengan kata kunci yang berbeda sesuai narasi sejarahnya masing-masing. Hasil dari memikirkan kembali tipologi ruang pamer museum dengan arsitektur naratif adalah ruang pamer yang tersusun berdasarkan urutan waktu kejadian sejarah yang edukatif, atraktif, dan inklusif.